PENGEMBANGAN MEDIA ANIMASI BERBASIS APLIKASI EMAZE UNTUK MENINGKATKAN LITERASI MEMBACA SEKOLAH DASAR - Windiyani , Tustiyana; Sarimanah , Eri; Abdul Gani, Resyi Abdul Gani; Mulyawati, Yuli; Karmilasari, Karmilasari; Agustiani, Tini (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Development of Emaze-Based Animated Media to Improve Reading Literacy of VI Students in the sub-topic My Friends Plants aims to (1) describe the process of developing Emaze-based animated video media to improve reading literacy; (2) describe the potential of Emaze-based animated video media to improve reading literacy. reading literacy and (3) describing student responses after using an Emaze-based animated video resource to improve reading literacy. The research methodology used is Research and Development with VI class students of SDN Pabuaran Cilendek Timur with the ADDIE model (Research, Design, Development, Implementation, Evaluation). The instruments used in this study were four experts, two interactive learning media experts, animation design media experts, EYD language experts and material experts, student and teacher response instruments, a questionnaire, and pre-test and post-test instruments. The validation results of the four experts produced an average of 97.3% with the criteria of